MAGNETIC-FIELD ALIGNED ELECTRIC FIELDS IN COLLISIONLESS SPACE PLASMAS - A BRIEF REVIEW - Fälthammar C.-G. (My University, 2004)
Magnetic-field aligned electric fields play an important role in the dynamics of magnetized plasmas. They allow decoupling of plasma elements by violation of the frozen field condition, breakdown of equipotential mapping, efficient acceleration of charged particles and rapid release of magnetic energy. In the collisionless plasmas that occupy most of the universe they used to be assumed nonexistent. A major consequence of the in situ measurements of the space age was the recognition that such electric fields do exist in the collisionless space plasma in spite of the absence of collisional friction. Indications of their existence came even from ground observations, but the final proof rests on the overwhelming evidence accumulated by in situ observations. These include observations of a number of characteristic features of particle distribution functions, various active experiments and direct measurements of electric fields. A number of mechanisms that can support magnetic field aligned electric fields have been identified. They include wave turbulence, solitary structures, magnetic mirrors, electric double layers and dynamic trapping. Some of them have been observationally confirmed to be important in the auroral process, but their relative roles are still not well known.
Keywords: Magnetic-field aligned; parallel electric fields